The Fisher Grade in predicting a degree of cerebral vasospasm in patients after intracranial aneurysm rupture - Đilvesi, Đula G; Cigić, Tomislav; Papić, Vladimir; Horvat, Igor; Karan, Mladen; Vuleković, Petar (Vojnosanitetski pregled, 2017)
Background/Aim. Intracranial aneurysms are pathological enlargement of the wall of cerebral arteries. Intracranial aneurysms rupture is a dramatic event with a significant morbidity and mortality. The Fisher Grade is widely accepted in assessment of the extensiveness of aneurysmal subarachnoid hemorrhage (aSAH) and the presence of other intracranial hemorrhage on the computed tomography (CT) scan. Significant early complication of a aSAH may be a cerebral vasospasm. The aim of this study was to determine the relationship between the extensiveness of aSAH, assessed by the Fisher Grade on admission, with the intensity of cerebral vasospasm in patients with ruptured intracranial aneurysm. Methods. This prospective clinical study included 50 patients with aSAH hospitalized at the Clinic of Neurosurgery, Clinical Center of Vojvodina, Novi Sad, Serbia. All the patients underwent 256-layer cranial CT and CT angiography on admission and on the day 9. Based on native CT scans, they were classified according to the Fisher Grade. On CT angiography images, intensity of cerebral vasospasm was determined. Results. On the basis of admission CT images, 24% of patients were classified into the Fisher Grade group 2, while 34% and 42% were in the groups 3 and 4, respectively. A positive correlation of the Fischer Grade on admission with the intensity of cerebral vasospasm was established, but with no statistical significance (ρ = 0.273, p = 0.160). Conclusion. This study showed that the Fisher Grade is not significant in predicting the intensity of cerebral vasospasm in patients hospitalized with intracranial aneurysm rupture.